2009
DOI: 10.1080/00207390903223754
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of teacher and lecturer perspectives on the transition from secondary to tertiary mathematics education

Abstract: The transition from school to tertiary study of mathematics comes under increasing scrutiny in research. This article reports on some findings from a project analysing the transition from secondary to tertiary education in mathematics. One key variable in this transition is the teacher or lecturer. This article deals with a small part of the data from the project -analysing secondary teachers' and lecturers' responses to questions on the differences they perceive between school and university and the importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 14 publications
1
20
1
2
Order By: Relevance
“…However, the authors concur with the findings of Hong et al (2009) who suggested that there are important roles for secondary teachers and tertiary lecturers to play in helping students with their transition. While higher education should not be a mere extension of second level education, there is a need for both teachers and lecturers to be aware of what is happening in each other's sectors to ensure a coherent approach to mathematics education in the transitionary stages.…”
Section: Resultscontrasting
confidence: 38%
See 4 more Smart Citations
“…However, the authors concur with the findings of Hong et al (2009) who suggested that there are important roles for secondary teachers and tertiary lecturers to play in helping students with their transition. While higher education should not be a mere extension of second level education, there is a need for both teachers and lecturers to be aware of what is happening in each other's sectors to ensure a coherent approach to mathematics education in the transitionary stages.…”
Section: Resultscontrasting
confidence: 38%
“…Undoubtedly there are important roles for secondary teachers and tertiary lecturers in helping students to ease these difficulties. However large scale research carried out in New Zealand has shown that there is a lack of communication between these two sectors and a lack of knowledge and awareness of what is happening in each other's courses (Hong et al, 2009). This study will investigate such findings from an Irish perspective and evaluate third level mathematics lecturers' awareness of and attitudes to the recent changes to the second level mathematics curriculum brought about by Project Maths.…”
Section: Insert Table 1: Project Maths Implementation Timelinementioning
confidence: 99%
See 3 more Smart Citations